The Moving Rubber Hand Illusion Reveals that Explicit Sense of Agency for Tapping Movements Is Preserved in Functional Movement Disorders - Marotta, Angela; Bombieri, Federica; Zampini, Massimiliano; Schena, Federico; Dallocchio, Carlo; Fiorio, Mirta; Tinazzi, Michele (Frontiers in Human Neuroscience, 2017)
Functional movement disorders (FMD) are characterized by motor symptoms (e.g., tremor, gait disorder, dystonia) that are not compatible with movement abnormalities related to a known organic cause. One key clinical feature of FMD is that motor symptoms are similar to voluntary movements but are subjectively experienced as involuntary by patients. This gap might be related to abnormal self-recognition of bodily action, which involves two main components: sense of agency and sense of body ownership. The aim of this study was to systematically investigate whether this function is altered in FMD, specifically focusing on the subjective feeling of agency, body ownership, and their interaction during normal voluntary movements. Patients with FMD (n=21) and healthy controls (n=21) underwent the moving Rubber Hand Illusion (mRHI), in which passive and active movements can differentially elicit agency, ownership or both. Explicit measures of agency and ownership were obtained via a questionnaire. Patients and controls showed a similar pattern of response: when the rubber hand was in a plausible posture, active movements elicited strong agency and ownership; implausible posture of the rubber hand abolished ownership but not agency; passive movements suppressed agency but not ownership. These findings suggest that explicit sense of agency and body ownership are preserved in FMD. The latter finding is shared by a previous study in FMD using a static version of the RHI, whereas the former appears to contrast with studies demonstrating altered implicit measures of agency (e.g., sensory attenuation). Our study extends previous findings by suggesting that in FMD: i) the sense of body ownership is retained also when interacting with the motor system; ii) the subjective experience of agency for voluntary tapping movements, as measured by means of mRHI, is preserved.